SAT0375 Chronic low back pain in osteoporotic females with rheumatoid arthritis a randomized clinical trial. (23rd January 2014) - Traistaru, R.M.; Rogoveanu, O.; Matei, D.; Popescu, R.
Abstract : Background: Chronic low back pain (LBP) is one of the most common symptom in osteoporosis rheumatoid arthritis patients leading to complex disability (1). Various therapeutic approaches (range-of-motion exercises and exercise programs) have been proposed for chronic low back pain in patients with rheumatoid arthritis and osteoporosis and can delay the loss of joint function and help keep muscles strong (2) Objectives: The aim of our study is to compare the effects of three therapeutic approaches in these patients in terms of pain, disability (severity of rheumatoid arthritis) and self-control of the complex disorders. We take into consideration the literature data about the evidence-based primary care options for chronic LBP. Methods: 67 females (mean age 42.8 years) with rheumatoid arthritis (mean disease duration 6.8 years) and osteoporosis (mean disease duration 3, 4 years) were randomized to the three groups in accordance to the type of treatment: I (23% of patients) - only medication, II (40% of patients) - medication + physiotherapy (TENS, interferential current, ultrasound), III (37% of patients) medication + aerobic training. The rehabilitation program was represented by 12 physiotherapy sessions and 18 aerobic training sessions (3 sessions/week). Outcome measures were VAS pain, DAS 28, BMD (T-Score), HAQ score and Arthritis Self-Efficacy Scale (ASES). All assessments were performed pre-post intervention and at six month follow-up. Results: All the groups showed similar decrease in pain on the third assessment and there was no significant difference between the groups. In the first and group the second there was a significant improvement in DAS28 values (p<0, 05) as well as HAQ (p<0, 05) after treatment. The third group also showed significant improvement in DAS28 value as well as ASES and T Score at six month follow-up (p<0, 01). Conclusions: All of the three therapeutic approaches were found to be effective in diminishing pain and disability in osteoporosis rheumatoid arthritis patients with chronic low back pain, but aerobic training was found to be more effective in improving bone mineral density (T-Score) and psychological status. Our results confirm the literature data - physical activity is an interesting therapy for the prevention and treatment of bone loss and osteoporosis because it has no adverse side effects, it is low cost, and it confers additional benefits such as postural stability and fall prevention. Type and duration of physical training must be individualized to each patient, in accordance with severity of rheumatoid arthritis. References: Cutolo M, Otsa K, Uprus M, Paolino S, Seriolo B. (Aug 2007). Vitamin D in rheumatoid arthritis. Autoimmun Rev 7(1):59–64. Scott DL, Wolfe F, Huizinga TW. Rheumatoid arthritis. Lancet. 2010 Sep 25;376(9746):1094-108. Disclosure of Interest: None Declared